Dextran-Coated Iron Oxide Nanoparticles Loaded with Curcumin for Antimicrobial Therapies - Cristina Chircov; Raluca-Elena Ștefan; Georgiana Dolete; Adriana Andrei; Alina Maria Holban; Ovidiu-Cristian Oprea; Bogdan Stefan Vasile; Ionela Andreea Neacșu; Bianca Tihăuan (MDPI AG, 2022)
The current trend in antimicrobial-agent development focuses on the use of natural compounds that limit the toxicity of conventional drugs and provide a potential solution to the antimicrobial resistance crisis. Curcumin represents a natural bioactive compound with well-known antimicrobial, anticancer, and antioxidant properties. However, its hydrophobicity considerably limits the possibility of body administration. Therefore, dextran-coated iron oxide nanoparticles can be used as efficient drug-delivery supports that could overcome this limitation. The iron oxide nanoparticles were synthesized through the microwave-assisted hydrothermal method by varying the treatment parameters (pressure and reaction time). The nanoparticles were subsequently coated with dextran and used for the loading of curcumin (in various concentrations). The drug-delivery systems were characterized through X-ray diffraction (XRD) coupled with Rietveld refinement, transmission electron microscopy (TEM), high-resolution TEM (HR-TEM), selected area electron diffraction (SAED), dynamic light scattering (DLS) and zeta potential, thermogravimetry and differential scanning calorimetry (TG-DSC), vibrating sample magnetometry (VSM), and UV-Vis spectrophotometry, as well as regarding their antimicrobial efficiency and biocompatibility using the appropriate assays. The results demonstrate a promising antimicrobial efficiency, as well as an increased possibility of controlling the properties of the resulted nanosystems. Thus, the present study represents an important step forward toward the development of highly efficient antimicrobial drug-delivery systems.